The Assyrian Dictionary of the Oriental Institute of the University of Chicago. Volume 10: M (1977)
Editorial Board: Miguel Civil, Ignace J. Gelb, A. Leo Oppenheim, Erica Reiner; A. Leo Oppenheim and Erica Reiner, Editors-in-Charge; Robert D. Biggs, Associate Editor with the Assistance of Johannes M. Renger and Marten Stol; Assistant to the Editors, Marjorie Elswick; ersch. 1978; DM 256,-.